POTENSI PENGEMBANGAN AGROWISATA STROBERI SEBAGAI PEMBERDAYAAN MASYARAKAT DI DESA OELBITENO - Habel Koinmanas; Linda Marlince Taka; Moshe Markhasi Rupilu (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Agrotourism has emerged as a strategic approach to rural development, offering significant potential to enhance community welfare through the utilization of local resources. Oelbiteno Village possesses considerable potential in strawberry farming; however, this resource has not yet been optimally developed as an agrotourism attraction. The development of strawberry-based agrotourism is expected to function as a mechanism for both economic and social empowerment of the local community. This study aims to examine the potential for developing strawberry agrotourism as a means of community empowerment in Oelbiteno Village. A qualitative research design with a descriptive approach was employed. The study was conducted in Oelbiteno Village, with participants consisting of strawberry farmers, village officials, and local community members selected through purposive sampling. The independent variable in this study is the potential of strawberry agrotourism, while the dependent variable is community empowerment. Data were collected through field observations, in-depth interviews, and documentation. The data were analyzed using qualitative analysis techniques, including data reduction, data display, and conclusion drawing. Triangulation was applied to ensure the validity and reliability of the findings. The findings reveal that Oelbiteno Village has strong natural, agricultural, and social potentials that support the development of strawberry agrotourism. Furthermore, the development of this sector has the potential to enhance community income, participation, and institutional capacity, provided it is managed in a well-planned and sustainable manner.